2022
DOI: 10.5194/essd-2022-128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The biogeography of relative abundance of soil fungi and bacteria in top surface soil

Abstract: Abstract. Fungi and bacteria are the two dominant groups of soil microbial communities worldwide. By controlling the turnover of soil organic matter, these organisms directly regulate the exchange of carbon between the soil and the atmosphere. Fundamental differences in the physiology and life history of bacteria and fungi suggest that variation in the biogeography of soil fungal and bacterial relative abundance could drive striking differences in carbon decomposition and soil organic matter formation across d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Waring et al (2013) have discussed how changes in soil conditions across biomes and land use affect the ratio of fungal to bacterial biomass, as differences in physiology affect the biogeographic distributions of these two groups. A recent study (Yu et al, 2022) showed that fungi with their generally slower growth and turnover rates (Rousk & Bååth, 2007), greater carbon to nutrient stoichiometry (Waring et al, 2013), and greater capacity to degrade more recalcitrant substrates (Strickland & Rousk, 2010) dominate in high latitudes with low mean annual temperature and high net primary productivity relative to soil bacteria that dominate in the tropical regions and in arable lands with frequent tillage disturbances.…”
Section: Water-driven Nutrient Inputs At Ecosystem Scalementioning
confidence: 99%
“…Waring et al (2013) have discussed how changes in soil conditions across biomes and land use affect the ratio of fungal to bacterial biomass, as differences in physiology affect the biogeographic distributions of these two groups. A recent study (Yu et al, 2022) showed that fungi with their generally slower growth and turnover rates (Rousk & Bååth, 2007), greater carbon to nutrient stoichiometry (Waring et al, 2013), and greater capacity to degrade more recalcitrant substrates (Strickland & Rousk, 2010) dominate in high latitudes with low mean annual temperature and high net primary productivity relative to soil bacteria that dominate in the tropical regions and in arable lands with frequent tillage disturbances.…”
Section: Water-driven Nutrient Inputs At Ecosystem Scalementioning
confidence: 99%